Role of trefoil factors in maintaining gut health in food animals - Fasina, Yewande O.; Obanla, Temitayo O.; Ekunseitan, Deji A.; Dosu, George; Richardson, Joseph; Apalowo, Oluwabunmi O. (Frontiers in Veterinary Science, 2024)
It is imperative to preserve the integrity of the gastrointestinal system in spite of the persistent existence of harmful chemicals and microbial flora in the gut. This is made possible by essential healing initiators called Trefoil factors which helps in mucosal reconstitution and tissue development on the gastrointestinal surface. The trefoil factors are a class of abundant secreted proteins that are essential for epithelial continuity (TFFs). Trefoil factor family (TFF) proteins are biologically active peptides that play significant role in safeguarding, restoring and continuity of the gastrointestinal tract (GIT) epithelium, through collaborative modulations with mucins in the mucosal layer. These peptides are readily produced in reaction to epithelial damage in the digestive tract, thereby contributing to the healing and restituting of the epithelial layers of the intestine. In addition, considerable evidence indicated that TFF peptides trigger proliferation, migration and angiogenesis, all which are crucial processes for wound healing. There is also increasing evidence that TFF peptides modulate the mucosal immune system. These protective properties, suggest that dietary manipulation strategies targeted at enhancing the expression and synthesis of TFF peptides at optimal levels in the GIT epithelium, may constitute a plausible alternative strategy to the use of in-feed antibiotic growth promoters to maintain epithelial integrity and promote resistance to enteric pathogens. This review describes TFF peptides, with importance to their biological functions and involvement in gastrointestinal mucosal protection and repair in food animals.